The Language of Chaos: Imagining Time in the Age of Pandemics. Issue 1 (1st April 2022) - Ares, Silvia G. Kurlat
Abstract : Historically, a wide variety of topics appear in discussions about pandemics, from medical issues to apocalyptic and religious visions. These themes can also be found in recent essays and literary fiction produced in Latin America. In this essay I argue that lack of distance and perspective from the COVID-19 pandemic seems to rob essays from any meditation about a freeing sublime imagery, or a cohesive vision for its thereafter. In other words, these deeply distressing events provide the backdrop for the emergence of radical figurative narratives that operate within/against what Tom Moylan would have called the emergence of apocalyptic hope. In contrast, postapocalyptic novels produced in Argentina since the turn of the century deal with these issues in a very different way. These novels showcase state projects that have imploded or are about to collapse, and where individual choices build the only possible forms of resistance should a future (be it dystopic or postapocalyptic) come into existence. In this essay I explore the different reasons allowing for this phenomenon: essays registering lived experiences and literature envisioning chaotic futures collide, and only the latter seems to be able to narrate our present in way that makes sense of the collective historic moment.